Incentive Policies for Traditional Fishermen to Enhance Their Welfare: A Perspective from The Theory of Dignified Justice - Rizky, Karo Karo (Universitas Muhammadiyah Surakarta, 2025)
Tujuan penulisan ini untuk menganalisis kebijakan insentif bagi nelayan tradisional untuk peningkatan kesejahteraannya. Metode penelitian yang digunakan adalah metode yuridis normatif menggunakan data sekunder, dan analisis kualitatif. Temuan penelitian ialah Nelayan tradisional sangat memerlukan perlindungan dan insentif. Kebijakan insentif memiliki legalitas dalam peraturan perundang-undangan di Indonesia. Nelayan tradisional memiliki kelemahan permodalan, dan kelemahan alat dalam melakukan penangkapan ikan. Penangkapan ikan oleh nelayan tradisional masih menerapkan perlindungan laut yang optimal. Rumusan masalah yang diangkat adalah Bagaimana model kebijakan insentif yang berbasis keadilan bermartabat dapat dirancang untuk meningkatkan kesejahteraan nelayan tradisional secara berkelanjutan dan memiliki kepastian hukum? Kebaruan penelitian adalah Kebijakan insentif ini memiliki kepastian hukum dan legalitas karena telah diamanatkan dalam Undang-Undang Perikanan, Undang-Undang Nomor 7 Tahun 2016 tentang Perlindungan dan Pemberdayaan Nelayan, Pembudi Daya Ikan, dan Petambak Garam, serta Peraturan Menteri Kelautan dan Perikanan Republik Indonesia Nomor 19 Tahun 2023 tentang Penyaluran Bantuan Pemerintah di Lingkungan Kementerian Kelautan dan Perikanan (Permen KKP 19/2023). Pemberian insentif ini juga dilakukan dengan pendataan dan administrasi yang ketat agar benar-benar tepat guna This scholarly endeavor aims to meticulously analyze incentive policies for traditional fishers with the objective of enhancing their welfare. The methodology employed for this research is normative juridical, relying on secondary data and qualitative analysis. The findings indicate that traditional fishers are in dire need of protection and incentives. Incentive policies possess legal standing within Indonesian regulatory frameworks. Traditional fishers frequently encounter limitations in terms of capital and fishing equipment. Notably, their fishing practices consistently demonstrate an optimal commitment to marine conservation. The central research question posed is: How can a dignified justice-based incentive policy model be designed to sustainably improve the welfare of traditional fishers and ensure legal certainty? The novelty of this research lies in the fact that this incentive policy is endowed with legal certainty and legitimacy, being mandated by the Fisheries Law, Law Number 7 of 2016 concerning the Protection and Empowerment of Fishers, Fish Cultivators, and Salt Farmers, and the Regulation of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number 19 of 2023 concerning the Distribution of Government Assistance within the Ministry of Maritime Affairs and Fisheries (Permen KKP 19/2023). Furthermore, the provision of these incentives is executed with stringent data collection and administrative procedures to ensure their precise and effective application.